Pengaruh Reinforcing Factors Terhadap Perilaku Pencegahan Hipertensi pada Pra Lansia Berisiko di Wilayah Kerja Puskesmas Tamalate Makassar - Hijrah hijrah; Andi Asrina; Hasriwiani Habo Abbas (PT.Mantaya Idea Batara, 2024)
Tamalate Public Health Center found the highest number of people with hypertension, namely during the last 3 years. In 2021, there were 11,963 cases; in 2022, 12,874 cases; and in 2023 (January-September), there were 10,158 cases. This study aimed to analyze the effect of reinforcing factors on hypertension prevention behavior in the pre-elderly at risk in the Tamalate Health Center in Makassar City. The type of research used is quantitative with a cross- sectional study approach consisting of 172 samples with a sampling technique, namely purposive sampling. Results of the study: There was an effect of reinforcing factors of social support (?=0.000) and support of health workers (?=0.002); There is no effect of reinforcing factors of government regulations (?= 0.111) on hypertension prevention behavior ?in at-risk pre-elderly (elderly) at the Tamalate Health Center in Makassar City. Education is essential to be carried out so that the contribution of all relevant parties is needed, not only health workers within the scope of the Public health center but also the participation of the government and the community in its application to support the preventive behavior movement for hypertension events, especially in the pre- at-risk elderly.